2015
DOI: 10.1111/jre.12307
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal healing with a preameloblast‐conditioned medium in dogs

Abstract: These results suggest that PA-CM has the potential to regenerate periodontal tissues in PDL and cementum defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Epithelial rests of Malassez in the periodontal ligament (PDL) also protect against resorption ( Keinan & Cohen, 2013). Periodontal research in dogs has shown that signalling molecules can significantly repair experimentally induced replacement resorption after damage to the cementum layer where it is hypothesized PDL cells differentiate into cementoblasts (Yu et al, 2016). It is therefore plausible that that signalling molecules and cytokines from REPs can affect not only the regeneration of pulp-like tissue but also enhanced mineralization and regeneration/repair of the roots affected with ERR.…”
Section: Toothmentioning
confidence: 99%
“…Epithelial rests of Malassez in the periodontal ligament (PDL) also protect against resorption ( Keinan & Cohen, 2013). Periodontal research in dogs has shown that signalling molecules can significantly repair experimentally induced replacement resorption after damage to the cementum layer where it is hypothesized PDL cells differentiate into cementoblasts (Yu et al, 2016). It is therefore plausible that that signalling molecules and cytokines from REPs can affect not only the regeneration of pulp-like tissue but also enhanced mineralization and regeneration/repair of the roots affected with ERR.…”
Section: Toothmentioning
confidence: 99%
“…In our previous studies, we aimed to regenerate the periodontium using dental epithelium‐derived factors. Preameloblast‐conditioned medium (PA‐CM) and Copine7 (CPNE7), a component of the PA‐CM, have been reported to regenerate the physiological structure of the PDL (Yu et al, 2016; Choung et al, 2019). CPNE7 treatment in three‐wall defect models resulted in rearranged PDL fibres in canines.…”
Section: Introductionmentioning
confidence: 99%
“…Esses achados sugerem que o selamento apical com tecido mineralizado tem uma orientação centrípeta, iniciando em regiões periféricas até o centro do forame, principalmente formado por cemento de tipo celular. A literatura que caracteriza a natureza do tecido mineralizado depositado no reparo apical após tratamento endodôntico é limitada, sendo o reparo do cemento mais estudado durante o tratamento ortodôntico (Mehta et al, 2017) e tratamento periodontal (Yu et al, 2016;Hernandez-Monjaraz et al, 2018).…”
Section: Discussionunclassified